PENTINGNYA SINERGITAS KELUARGA DENGAN SEKOLAH MELAKSANAKAN STRATEGI DALAM PEMBELAJARAN - Putu Sanjaya (Widyacarya: Jurnal Pendidikan, Agama dan Budaya, 2019)
Education is a process that involves many people, and is the responsibility of everyone.In the process of education requires a strategy that is implemented in teaching and learningactivities with a view to be able to realize the objectives of learning with more optimal. Theprocess of education does not only happen in the school environment, but happens, even moreso, in the family environment. It means that both the family and the school share responsibilityfor education. Therefore it takes a synergy between family and school in achieving educationalgoals.Keywords: Education, Family, School